Protes Sosial Masyarakat Parean Girang, Indramayu terhadap Relokasi Peternakan Babi (1995-1996) - Wahyu Iryana (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
Since 1995-1996 in Parean Girang Kandanghaur Indramayu there was accident the rejecting of the pig cattle relocation. That history actually from a wish investor to make it happen in Jakarta, but because there is no area therefore overwhelmed in West Java Governance to take in Bogor, Tanggerang, Lebak, Bekasi, and also Karawang will be taken for cattle of pig, but the regents of all countries to refuse it. Therefore a side of the governor Indramayu is welcome of making permission for the investor to open the cattle of pig relocation in their country. Therefore the cattle of pig is undertaken in Indramayu actually in Parean Girang, well this moment making reaction for public in Parean Girang where unwillingness on the decision for the governor. The purpose of this thesis is to address to present Sartono Kartodirjo, history is causality contact was start from social fluctuation where making the community disturbance and social changes. On this matter comprises many factor Values, Economy, Religius, Politic, Social-culture on Social-structure. We can said that to create a Necassery Condition and Sufficient Condition. The thesis explained a comparation of these perspectives and theories responses, as follow 1) To know how well-understood backround the arise cattle of Pig in Parean Girang Kandanghaur 2) To understanding action of refusing cattle of a pig in Paren Girang Kandanghaurfor making a pig relocation. The thesis used with history of metodolgy is method to study accident in the past to purpose making reconstruction of objective and systematic history. The methods is comparations with Heuristic, Critic, Interpretation, and Historiografy. The thesis to try express well-understood being history of refusing a Pig relocation in Parean Girang since 1995-1996. Start from moving a cattle of pig relocation process from Jakarta to Indramayu where it is making polemic and protest being various community, because of Economy, Relgious, Politic, and Sosila-culture. It is making unwillingness for community, where finished on decided latter of negation from MUI No: 08/MUI-Kec/VI/1995 its sense to object to that cattle of a pig relocation. This has led community initiatives Parean Girang village District of Kandanghaur tounder take preventive measures rejecting the relocation ofpig farms. Various ways have been made include working withthe media, Ngosor Islamic organizations, issued astatement, and the demonstrations that led to the revolution in Indramayu Regional Government on 29 April 1996.